EP1160 Prognostic factor in primary vulvar squamous-cell cancer in the context of FIGO 1988 and 2009 and Brigham and women's vulvar tumor classification system. (1st November 2019) - Ferrari, F; Forte, S; Bonetti, E; Sartori, E; Odicino, F
Abstract : Introduction/Background: The aim of the study is to identify prognostic factors associated with poor outcomes in vulvar squamous-cell cancer and to compare the prognostic discrimination of FIGO 1988 and FIGO 2009 staging systems with the new Brigham and Women's Vulvar Tumor Classification system (BWVTC). Methodology: We retrospective evaluated patients with vulvar squamous-cell carcinoma treated with primary surgery at Spedali Civili of Brescia (Italy) from January 2005 to December 2015. We collected dmeographic data and relevant prognostic factors such as age, tumor size, length of free surgical margin in millimeters, depth of invasion (DOI) in millimiters, presence of perineural invasion (PNI), lymph vascular space invasion (LVSI) and lymph nodal status. We used logistic bivariate regression models to investigate survival outcome. We developed multivariate regression Cox models for survival in FIGO 1988, 2009 and BWVTC using significant risk factors. Results: We found a total of 123 patients. We identified five relevant risk factors as follows: DOI > 9 mm (HR 2.9 - CI95% 1.10–8.35; p=0.04), PNI (HR 15 - CI95% 4.34–51.82; p=0.00), LVSI (HR 5.3 - CI95% 1.74–15.82; p=0.00), free surgical margin <8 mm (HR 4.9 - CI95% 1.02–23.31; p=0.04) and positive lymph nodes (HR 6.3–1.81–22.11; p=0.00). Multivariate regression Cox models were not significant for FIGO 1988 (p=0.20) and 2009 (p=0.24); in FIGO 2009, positive lymph node status was excluded from analysis as factor since its direct correlation with stage. In BWVTC two factors resulted significant: PNI (HR 4.17; CI95% 1.19–14.65; p=0.02) and positive lymph node (HR 4.24; CI95% 1.23–14.63). Conclusion: PNI and positive lymph nodes remain the most important prognostic factors in vulvar cancer, regardless staging system. Disclosure: Nothing to disclose